Short Communication: changes in gait after 12 wk of shoeing in previously barefoot horses. (16th November 2022) - Panos, Katelyn E; Morgan, Kristin; Gately, Rachael; Wilkinson, Julia; Uden, Alexandra; Reed, Sarah A
Abstract: Farriery can impact gait symmetry and lameness outcomes, but there is limited scientific data documenting these effects. We hypothesized that shoeing previously barefoot horses with plain stamp shoes on the hind hooves would increase gait symmetry, alter hock angles and increase range of motion, and improve lameness scores more than shoeing with traditional fullered shoes. At the start of the study, gait symmetry via wireless inertial motion sensors (IMS), kinematic gait analysis (hock angle and range of motion), and American Association for Equine Practitioner's (AAEP) lameness scoring were completed for 14 barefoot horses. Horses were then trimmed and hind hooves were shod (wk 0) in three-quarter fullered shoes or plain stamp style shoes. Horses were trimmed and re-shod at week 6. At the end of 12 wk, the IMS analysis, kinematic gait analysis, and lameness scoring were repeated. Differences between shod and barefoot values were calculated for each horse, and impact of shoe type was analyzed via t -test. Significance was determined at P ≤ 0.05. No differences were observed in the IMS scores, hock angles or range of motion, or AAEP lameness scores between horses shod in fullered or plain stamp shoes ( P ≥ 0.08). As no variables were determined to be significantly different between the two shoe types, data from all horses were combined to analyze the differences between the barefoot and shod state. Shoeing increased the maximum angle of the right and left hocks ( P ≤ 0.03) and the minimum angle of the left ( P = 0.02) but not right hock ( P = 0.23) relative to barefoot conditions. No differences in hock range of motion were observed in either hock. Lower AAEP lameness scores were observed in horses when shod compared with barefoot ( P = 0.001). In conclusion, shoeing previously barefoot horses improved AAEP lameness scores and increased hock angles, regardless of the type of shoe. Abstract : Shoeing previously barefoot horses alters gait characteristics at the trot. Lay Summary: Horses are athletic animals whose quality of movement affects their ability to perform. Management of hooves can influence gait symmetry. Shoeing horses is an accepted standard of care for athletic animals. Here, we show that shoeing previously barefoot horses using industry accepted farriery protocols increased maximum hock angles at the trot and reduced lameness scores.